"This Time It's Different" Generative Artificial Intelligence and Occupational Choice - Daniel Goller; Christian Gschwendt; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, we show the causal influence of the launch of generative AI in the form of ChatGPT on the search behavior of young people for apprenticeship vacancies. There is a strong and long-lasting decline in the intensity of searches for vacancies, which suggests great uncertainty among the affected cohort. Analyses based on the classification of occupations according to tasks, type of cognitive requirements, and the expected risk of automation to date show significant differences in the extent to which specific occupations are affected. Occupations with a high proportion of cognitive tasks, with high demands on language skills, and those whose automation risk had previously been assessed by experts as lower are significantly more affected by the decline. However, no differences can be found with regard to the proportion of routine vs. non-routine tasks.
Keywords: J24; O33; 330; artificial intelligence; occupational choice; labor supply; technological change